The role of cadre in the community on diabetic retinopathy management and its challenges in low-middle income countries: a scoping review - Irma Suwandi Sadikin; Yeni Dwi Lestari; Andi Arus Victor (BMC, 2024)
Abstract Introduction Diabetes is a serious public health problem, with low- and middle-income countries (LMICs) bearing over 80% of the burden. Diabetic retinopathy (DR) is one of the most prevalent diabetic microvascular problems, and early diagnosis through eye screening programs for people with diabetes is critical to prevent vision impairment and blindness. Community-based treatments, including non-physician cadres have been recommended to enhance DR care. Methods The review protocol was determined and scoping review was conducted.The population, concept, and context were "cadre", "role of cadre in the management of DR", and LMICs". Data were collected from databases and searches, including grey literature. Results Cadre can motivate people to attend a diabetic eye screening event when the rate of eye examinations is about six times higher than before the start of the intervention. Health education is a possible area for task sharing, and the cadre reported could also perform the task of vision testing. The cadre could be a good supporter and a good reminder for society. However, several challenges have been faced in this study and inadequate infrastructure is the foremost challenge found in this study. Other challenges encountered in the studies include poverty, lack of community awareness, trust issues, and low education levels contributing to poor health. Conclusion The current study highlighted significant gaps in the literature, which focus on the role of cadre as a community-based intervention in managing DR in LMICs. Further research is needed to develop evidence to support cost-effective screening services and cadre-related policy development in LMICs.